A Review of Lightning Protection System - Risk Assessment and Application - Hui Hwang Goh; Sy yi Sim; Jamil Shaari; Noor Atiqah Azali; Chin Wan Ling; Qing Shi Chua; Kai Chen Goh (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
A lightning strike could bring thousands mega-ampere of current in a blink of eyes. As a result, a failure of grounding the strike may cause serious damage to the home and industrial appliances and gadgets. Hence, a lightning protection system is essential to the current transmission system. Lighting is a natural phenomenon that is unavoidable. Hence, the study of the properties and characteristics of lightning is a must in designing lighting protection system. Every application has different criteria to be fulfilled. The type of lighting protection system is categorized based on the location and user. The different of location is a public area, transportation system, power system transmission and generation system which include renewable energy source. Each area can conclude different level of protection. This paper is assessing the possibility and probability of transient impact on all applications including, public area, power system line, and generating system. The review includes countermeasure which addressed few steps to determine the effect of lightning and countermeasure of protection.